Optimasi Pengelolaan Persediaan dalam Menangani Perbedaan Stok di Website dan Gudang Online Nibras - Nur Izzatusshafa An-Nisaa; Intan Ullyatul Fasyah; Hariyanto Hariyanto (STIKes Ibnu Sina Ajibarang, 2025)
In the ever-evolving e-commerce era, the Nibras Online Warehouse plays a crucial role in supporting the distribution of Muslim clothing products throughout Indonesia. This strategic role demands an accurate and efficient inventory management system to ensure smooth and timely order fulfillment. One of the main challenges faced is the discrepancy between inventory data recorded on the website and the actual physical stock available in the warehouse. This discrepancy not only impacts delivery delays but also has the potential to reduce customer satisfaction and the company's overall image. This study aims to analyze the root causes of the inventory management system and develop practical solutions to ensure data consistency between the digital system and real-world conditions. The methods used include literature review, direct field observations, in-depth interviews with warehouse staff, and documentation of daily operational processes. Through an analytical approach using the 5 Whys method and a fishbone diagram, it was found that factors such as delays in data input, lack of synchronization between the operational and IT divisions, and an undocumented goods receipt process were the main causes of inventory data discrepancies. To address this, it is recommended to implement a real-time technology-based inventory management system integrated with the online sales system. Additionally, training warehouse employees on new standard operating procedures (SOPs) and regular stock audits are crucial steps to create transparency and efficiency. These steps are expected to improve data accuracy, accelerate decision-making, and support sustainable business growth. Regular evaluations are also necessary to ensure the implemented system remains relevant and adaptable to the dynamics of warehouse operations.